A good practice guide for translating and adapting hearing-related questionnaires for different languages and cultures - Hall, Deborah A.; Domingo, Silvia Zaragoza; Hamdache, Leila Z.; Manchaiah, Vinaya; Thammaiah, Spoorthi; Evans, Chris; Wong, Lena (Taylor & Francis, 2018)
Objectives: To raise awareness and propose a good practice guide for translating and adapting any hearing-related questionnaire to be used for comparisons across populations divided by language or culture, and to encourage investigators to publish detailed steps. Design: From a synthesis of existing guidelines, we propose important considerations for getting started, followed by six early steps: (1) Preparation, (2, 3) Translation steps, (4) Committee Review, (5) Field testing and (6) Reviewing and finalising the translation. Study sample: Not applicable. Results: Across these six steps, 22 different items are specified for creating a questionnaire that promotes equivalence to the original by accounting for any cultural differences. Published examples illustrate how these steps have been implemented and reported, with shared experiences from the authors, members of the International Collegium of Rehabilitative Audiology and TINnitus research NETwork. Conclusions: A checklist of the preferred reporting items is included to help researchers and clinicians make informed choices about conducting or omitting any items. We also recommend using the checklist to document these decisions in any resulting report or publication. Following this step-by-step guide would promote quality assurance in multinational trials and outcome evaluations but, to confirm functional equivalence, large-scale evaluation of psychometric properties should follow.